(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2007)
The lower Eocene Roda Sandstone (Figols Group, south-central Pyrenees) mainly consists of mouth bars and delta-front sandstone lobes deposited in a flood-dominated river-delta system. The deposition of these bodies was strongly controlled by an interaction between flood-dominated gravity flows entering seawater, topographic confinement and tidal currents. The Roda Sandstone is made up of six depositional sequences of different hierarchical order each of which is characterized by a basal deltaic sandstone wedge (R1 to R6) that passes upward into a siltstone and mudstone interval. Each basal deltaic sandstone wedge is composed of three types of facies association and respective facies tract (sensu Mutti 1992) that, from proximal to distal zones, are indicated as T1, T2 and T3. These three facies tracts are created by the downcurrent evolution of different types of sediment-laden stream flows entering seawater and related hyperpycnal flows. Their deposits are constituted by three different types of coarse-grained mouth bars and corresponding fine-grained delta-front sandstone lobes. The tidal influence is present in facies tract T3 in the R5 and R6 sandstone units, where the passage between flood-dominated mouth bars and the delta-front sandstone lobes occurs through intermediate facies characterized by different types of sigmoidal-cross stratification whose meaning will be discussed. The basal deltaic sandstone wedges of Roda sandstone are characterized by a progressive forestepping culminating in the R6 unit that erodes the underlying R5 unit and by an overlying backstepping unit indicated as R7. The erosive surface at the base of R6 unit is interpreted as a sequence boundary that divides the Roda Sandstone into two parts: 1) an underlying highstand system tract (HST) and falling stage system tract (FSST) (units R1 to R5) and 2) an overlying low-stand delta (the R6 unit) that passes upward into highstand mudstone through a transgressive system tract represented by the R7 unit. Pdf